A comparative study on the selection of new characters in Chinese primary school textbooks in mainland China and the Taiwan region - Xiaofang Ma (Heliyon)
The selection of new characters for Chinese textbooks is essential for primary school literacy teaching. This research used content and comparative analyses to study the selection of new characters for Chinese textbooks used in primary schools in mainland China and the Taiwan region. The results showed that there were more new characters in the Chinese primary school textbooks used in mainland China than in those used in the Taiwan region. The distribution of new characters in the textbooks used in each region also differed, and their presentation varied significantly depending on whether they were compiled in mainland China or the Taiwan region. Furthermore, few characters were common to the textbooks used in mainland China and the Taiwan region. These findings provide important references for the study of new characters in textbooks and ultimately for literacy teaching in primary schools.